Sexual Harassment Among Nepali Non-Migrating Female Partners of International Labor Migrant Men - Gyawali, Kalpana; Simkhada, Padam; van Teijlingen, Edwin R.; Manandhar, Shraddha; Silwal, Ram Chandra (Journal of Health Promotion, 2023)
International migration shows an increasing trend around the world. The majority of labor migrants, particularly low/semi-skilled migrants from low- and middle-income countries, immigrate to destination countries leaving their family members behind, leading to an increasing number of transnational families. While non-migrating spouses often receive financial support in the form of remittances, their husbands’ migration also creates numerous social and personal problems. This general qualitative study aimed to explore non-migrating spouses’ experience of sexual harassment/abuse and its impact on their mental health. Fourteen in-depth interviews were conducted to collect data. Participants reported experiencing harassment by men they knew, including their teachers and colleagues, who knew their husbands were abroad. None of the women reported taking any action against the perpetrators. Policy level changes to spread awareness on sexual harassment, encouraging victims to report such acts, and establishing and implementing appropriate laws are essential to mitigate this serious problem.